Forage networks - Lazier, John R. (International Livestock Centre for Africa, 1986)
Describes the characteristics of networks and discusses their advantages. Presents the organisation and objectives of several forage networks. Examines the Forage Network in Ethiopia and the Pasture Network for Eastern and Southern Africa.